Discovery of the genus Pseudepione Inoue, 1943 in Taiwan, with description of a new species (Lepidoptera: Geometridae: Ennominae) - Wu, Shipher (Zootaxa, 2018)
The genus Pseudepione Inoue, 1943 is a small geometrid taxon comprising only two species, the typo species P. magnaria (Wileman, 1911) and P. shiraii Inoue, 1943. They are known to distribute in Japan (Honshu, Kyushu and Shikoku), south and central Korea (Choi 2012; Choi & An 2010; Jung & Oh 2012), the former species was also reported in Jiangxi of China (Fang 2003). The genus seems to be univoltine since adults can only be found in the autumn season (Wileman 1911; Inoue 1943, 1982; Parsons et al. 1999; Kim & Beljaev 2001; Sato 2011; Choi 2012). The combination of the absence of forewing fovea, tuft of scales of third abdominal sternite, gnathos, socii and cormata is quite unique in Ennominae. So far, the phylogenetic affinity of Pseudepione is unclear since the closely related genus has never been proposed and still no morphological or molecular phylogenetic studies, i.e. Beljaev (2006a; 2006b; 2016), Sihvonen (2011), Yamamoto & Sota (2007), Jiang et al. (2017), considering the palaearctic subfamily or tribal levels sampled this genus. The dense fundamental surveys conducted in recent 7 years in the cloud forests of Taiwan acquire the opportunity to collect this genus new to Taiwan. After comparing the Taiwanese specimens with the known two species in both sexes, it’s clear the Taiwanese specimens are a distinct species needed to be described in the present study.